Publishing Costs (re article processing charges, waivers and discounts) for Authors, Editors and Publishers: HESI SDG Publishers Compact Fellows Top Action Tips (ScienceOpen Research)
A 'waiver' is a discounted or free Article Processing Charge (APC). Be aware that waivers do not always translate into offers for removing all Article Processing Charges for a particular author or submitted manuscript type. For background information on increasing equity and open access see OASPA. This document contains information for authors, editors and publishers. For authors, the tips help understand how to find waivers and discounts to remove or lower the barrier of publishing costs for open access. For editors and publishers, the tips show how to help enable authors to access a journal’s information on waivers and discount processes. To be read in conjunction with the Top Action Tips for Promoting Equity